배양된 토끼 각막상피세포에 대한 Diclofenac Sodium 의 독성연구 - 손원섭; 진경현; Kyung Hyun Jin (Daihan angwa haghoi jabji, 1998)
Diclofenac sodium 점안제는 백내장수술 또는 액시머레이저 굴절교정각막절제술 후 환자의 염증 및 통증감소를 위하여 널리 사용되는 약제이나 수술 후 환자에 사용할 때 각막상피의 손상을 볼 수 있어 저자들은 토끼 각막상피를 세포배양 및 조직배양하고 세포수 및 조직에서 자라나온 집락의 넓이를 측정하여 각 농도별 diclofenac sodium의 각막상피세포에 대한 증식억제효과를 알아보았다. 세포배양에서 저농도(12.5, 25, 50, 100ug/ml)로 장기간 노출시 세포수가 48시간 후에 100ug/ml에서, 72시간 후에 50ug/ml와 100ug/ml에서 통계학적으로 의미있게 대조군에 비하여 감소되어 있었고, 고농도(0.1, 0.2%)로 2분간 한 번 노출시키고 5일 후 측정한 경우에서 는 0.1, 0.2ug/ml 모두에서 세포수가 대조군에 비해 통게학적으로 의미있게 감소되었으며 농도에 비례하였다. 조직배양에서는 위와 같은 저농도로 장기노출시는 50ug/ml 이상에서 대조군에 비해 조직에서 자라나온 상피의 면적이 작았고, 고농도로 2분간 접촉한 경우는 대조군에 비해 의미있는 차이는 없었다. 결론적으로 diclofenac sodium은 토끼 각막상피세포에 대한 증식억제효과 및 세포이동억제효과가 있으며 술 후 과용량 사용은 각막상피세포의 손상을 일으킬 수 있으므로 주의해야 할 것이다(한안지 39:1087-1094, 1998). Diclofenac sodium is a widely used drug for reducing inflammation and pain after cataract, surgery or excirner laser photorefractive keratectomy. However,we could find epithelial defect while using this drug postoperatively. To investigate the toxic effects of diclofenac sodium, we cultured corneal epithelial cells and tissues, then exposed them to various concentratiotration of drugs and measured the cell number and expanding area from. the original corneal tissue. In cases of cell culture, the cell number was counted at 24, 48, and 72 hours` exposure to l2.5, 25, 50, and 100 ug/ml solution of diclofenac sodium and at. 5 days after two minute exposure to 0. I and 0.2% solution. The cell number was reduced significantly at 50ug/ml (72 hrs later) , 100ug/ml(48 or 72 hrs later) and 0.1, 0.2% of solution than that of the control group. In tissue culture, we exposed the epithelial tissue to the same condition of cell culture. In long duration exposure conditions, the size of the epithelium grown from the tissues was smaller than that in the control group, especially at the dosage of 50 and 100ug/ml. In short duratio끄(2 minutes) exposure conditions, no significant difference from the control group wasfound. In conclusion, diclofenac sodium has some suppressive effects on the growth and migration of the rabbit corneal epithelium and its postoperative high dose or frequent instillation might injure the corneal epithelial cells (J Korean Ophthalmol Soc 39:1087-1094, 1998).